Influence of supercritical fluid extraction on lignocellulosic plant matrix and extractive substance yield - Zakharchenko, Alexandra V.; Bazarnova, Natalya G. (Acta Biologica Sibirica, 2022)
Natural substances of plant origin are widely used in pharmacies. However, the quantitative content of biologically active substances in plant cells is insignificant and the currently available extraction methods do not allow for the complete extraction of biologically active substances as a result of the strong lignocellulose matrix of the cell. Therefore, it is necessary to look for new extraction methods that increase the yield of extractive substances from plant raw materials. This paper is devoted to the effect of supercritical fluid extraction on the quantitative content of extractives contained in a plant cell. The study aims to establish the effect of supercritical fluid extraction on the lignocellulose matrix and the yield of extractive substances. The plant biomass of the vegetative part of the narrow-leaved cypress (Chamaenerion angustifolium L., Scop., 1771); roots and rhizomes of the stinky bug (Actaea cimicifuga Schipcz., J Compton); roots and rhizomes of the golden root (Rhodiola rosea L., 1753) were used as research objects. The extractive substances were extracted by sequential liquid extraction, supercritical fluid extraction, and a combination of these methods. To extract the maximum amount of extractives, the following solvents were used: a nonpolar solvent (hexane, 70% ethanol) and a highly polar solvent (water). Extraction of plant materials with supercritical CO₂ was carried out in a SFEU-5/2 laboratory setup with the following parameters: pressure (P), 350 bar; temperature (T), 60 °C; extraction time (t), 180 min. The comparison of the yield of extractive substances obtained by sequential liquid extraction and aqueous alcoholic extraction with the preliminary processing of raw materials with supercritical CO₂ shows that treatment with supercritical carbon dioxide activates the plant matrix; therefore, the content of the extracted components increases.